Кот да Винчи. Ограбление банки: повесть - сказка / К. Матюшкина - Матюшкина Катя (АСТ, 2014)
Экземпляры: ДО мл.аб. (20140710) / Инвентарный номер: 50686 / Цена: 294. 00. / Сис.шифр: Р2 / Авт.знак: М 35 / ББК: 84(2Рос=Рус)6